Importance of vitamin D and its receptor in sportsman health and athletic performance - ULUCAN, KORKUT (MARMARA UNIV, INST HEALTH SCIENCES, 2015)
Vitamin D is an important molecule which regulates many reactions in different tissues and organs, and also can be named as hormone. It can be synthesized either endogenously under UV light or exogenously by diet. Vitamin D is converted to its active form after being metabolised by liver and kidney, respectively. Blood 25-hydroxy vitamin D is the main metabolite that determines the individuals vitamin D levels. Vitamin D deficiency may lead to many diseases like diabetes, various cancer types and cardiovascular problems. They affect the target organs by triggering their vitamin D receptors. Many studies were carried out regarding the polymorphisms on the receptor gene, and outlined the function of the gene. Studies on athletes in different sport types showed the importance of this vitamin for athletic performance. Studies including the vitamin D blood levels and polymorphisms on the encoding gene associated the athletic performance and vitamin D, and low vitamin D blood levels and sports injuries were came into prominence. Fok1, Bsm1, Taq1 and Apa1 are the main examined polymorphisms within the gene. In this review, we aimed to give brief information about vitamin D, and state the importance of vitamin D metabolism and its receptor in the terms of sportsmen health. Therefore, we hope that this review will help scientists to have a general information about vitamin D and athlete health and performance; also will guide for further studies.
Keywords: Vitamin D; sport; athletic performance; sportsman health; 25-HYDROXYVITAMIN D; GENE POLYMORPHISMS; MUSCLE STRENGTH; SKELETAL-MUSCLE; D DEFICIENCY; GENOTYPE; QUADRICEPS; FOKI; MASS